Answers

  • Brainly User
2014-05-19T13:01:48+05:30
By simplifying
1 - 2ab - a² - b² 
1 - (a² + 2ab + b²) 
1 - (a + b)² 
wkt , (a² - b²) = (a+b)(a-b) 
as 1 = 1² 
1² - (a+b)² = [1+(a+b)]*[1-(a+b)] 
= (1+a+b)(1-a-b) 
1 5 1
@Sweety...I think you should go through your answer once again...
1-2ab-(a^2-b^2)
on simplyfing... 1-2ab-a^2+b^2....so all the step goes wrong after..
sh*t sry i didn't see it ,let me check it
2014-05-19T13:11:23+05:30
1-2ab- a^{2}+ b^{2}
1-2ab+ b^{2}- a^{2}
1-2ab+(b+a)(b-a)

I think this is to which I can factorize it...
0